Interlaminar Adhesive Strength of Nano-Reinforced Glass/Epoxy Laminates - Silva, H. (2015)
Interlaminar fracture is significantly influenced by the adhesive strength of fiber=matrix interfaces. Critical strain energy release rate (GC) is the most common parameter used to quantify the interfacial strength. However, subcritical debonding can occur at lower mechanical loads than those required for interlaminar fracture toughness (IFT). This study was performed using nanoclayreinforced epoxy=glass fiber laminates in order to analyze the influence of the addition of nanoclay and hydro aging on IFT and subcritical crack growth. Hydro aging was done immersinga batch of specimens in distilled water at 25 C for 30 days. Mode I IFT was significantly improved by the incorporation of nanoclays into the resin, the improvement reaching 31% for 3% of nanoclays content. The results of subcritical debonding were plotted in terms of da=dt versus G curves, for dry materials and long term hydro aged composites. Hydro aged composites exhibit not only a reduction of GIc, of about 14% for 3% of nanoclays, but also a higher subcritical crack propagation rate. The addition of nanoparticles reduces subcritical crack propagation rate.